Research developments in wood engineering and technology - Aguilera, Alfredo, 1964-; Davim, J. Paulo (Engineering Science Reference, an imprint of IGI Global, 2014)
"This book examines the latest research advances and technological developments for wood material as an engineering product and the innovation it provides for environmental friendly materials"--Provided by publisher.
Keywords: Wood.; Wood -- Testing.; elektronické knihy; electronic books